Solitary fibrous tumor of the thigh with epithelioid features: a case report - Garcia-Garcia Jose; Gozalbo Francisco; Pérez-Vallés Ana; Martorell Miguel; Gutierrez Jair; Gaona John (Diagnostic Pathology, 2007)
Abstract Background Extrapleural Solitary Fibrous tumors (SFTs) have been increasingly reported. The retroperitoneum, deep soft tissues of proximal extremities, abdominal cavity, trunk, head and neck are the most common extraserosal locations reported. Microscopically they show a wide range of morphological features, and so the differential diagnosis is extensive. Immunohistochemically, they commonly express CD34, vimentin, bcl-2 and CD99. Epithelial membrane antigen (EMA) and smooth muscle actin (SMA) may occasionally be expressed. Epithelioid morphology in extrapleural SFT has only very occasionally been described (five cases reported), some of them with biphasic pattern and others with malignant characteristics. Case presentation A SFT of the thigh with epithelioid areas in a 63 year old woman is reported. Microscopically the tumor showed areas hypo and hipercellular. At the periphery of the hipercellular areas there were nodules composed of epithelioid cells. Immunohistochemically both the spindle and epithelioid cells were positive for CD34, vimentin, bcl-2 and CD99. Epithelial, neural and muscular markers were negative. Molecular study was done and ruled out a synovial sarcoma. Conclusion Ten cases of SFT of the thigh have been reported but to our knowledge this is the first case with epithelioid morphology affecting the extremities. Identification of this pattern of SFT is of importance, to avoid misdiagnosis with other more aggressive conditions in soft tissue.